Gender Discrimination in Indonesian Labor Law: A Juridical Analysis of the Job Creation Law - Mhd Fikri Muzaki; Muhammad Arifin; Mhd Fauzan Azizi Sipahutar; M Fahmi Aulia Saragih Turnip; Anzalika Putri Ramadani (ISNU Sumatera Utara, 2026)
The enactment of Law Number 11 of 2020 concerning Job Creation has important implications for the labor protection system in Indonesia, including in efforts to realize gender equality in the work environment. Normatively, the principle of equal rights and prohibition of discrimination is still recognized in the framework of national labor law. However, the changes in regulations introduced through the Job Creation Law raise a number of problems related to the protection of women workers. This study aims to examine the regulation of gender equality in Indonesian labor law after the enactment of the Job Creation Law, identify provisions that have the potential to give rise to gender discrimination, and assess the effectiveness of these laws in preventing injustice against women workers, especially in the aspects of wages, promotions, and working conditions. The research method used is normative juridical with a regulatory approach and a conceptual approach. The results of the study show that although the Job Creation Law does not expressly contain discriminatory norms, some regulations related to labor relations flexibility and the wage system have the potential to have a greater impact on women workers. In addition, weak supervision and law enforcement cause the effectiveness of this law in preventing gender discrimination to be suboptimal. Therefore, it is necessary to strengthen implementing regulations and employment policies that are oriented towards gender justice.